2019
DOI: 10.1111/jcmm.14677
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of interferon regulatory factor 2 binding protein 2 suppresses gastric cancer progression by negatively regulating connective tissue growth factor

Abstract: Interferon regulatory factor 2 binding protein 2 (IRF2BP2) is a transcriptional repressor involved in regulating gene expression and other biological processes, including tumorigenesis. However, the clinical significance and roles of IRF2BP2 in human gastric cancer (GC) remain uncertain. Clinical GC tissues were obtained from GC patients at the First Affiliated Hospital of Nanchang University. Immunohistochemistry (IHC) was conducted to detect the IRF2BP2 protein in clinical paraffin specimens. Cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
(158 reference statements)
0
13
0
Order By: Relevance
“…Additionally, GC cells expressing IRF2BP2 shRNA were inoculated subcutaneously in mice to construct xenograft models, and the results showed that knocking down IRF2BP2 significantly inhibited tumor growth. This study demonstrated that IRF2BP2 knockdown decreased cell proliferation by inhibiting the binding of TEAD4 to YAP1, which then could no longer promote the transcription of genes downstream of YAP1, such as CTCF, an important oncogene related to the promotion of GC cell proliferation ( Yao et al, 2019 ). It important to note that, the differences in cellular proliferation phenotypes observed in previous studies may be associated with the different interaction partners and/or target genes of the IRF2BP2, which may be involved with the type of cell and tumor involved.…”
Section: Irf2bp2 In Cell Proliferationmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, GC cells expressing IRF2BP2 shRNA were inoculated subcutaneously in mice to construct xenograft models, and the results showed that knocking down IRF2BP2 significantly inhibited tumor growth. This study demonstrated that IRF2BP2 knockdown decreased cell proliferation by inhibiting the binding of TEAD4 to YAP1, which then could no longer promote the transcription of genes downstream of YAP1, such as CTCF, an important oncogene related to the promotion of GC cell proliferation ( Yao et al, 2019 ). It important to note that, the differences in cellular proliferation phenotypes observed in previous studies may be associated with the different interaction partners and/or target genes of the IRF2BP2, which may be involved with the type of cell and tumor involved.…”
Section: Irf2bp2 In Cell Proliferationmentioning
confidence: 97%
“…Interferon regulatory factor 2-binding protein 2 is extensively involved in regulating gene expression and other biological processes, including metabolic syndrome, nervous diseases, immunodeficiency disorders, and cancer. Recent data suggest the participation of IRF2BP2 in controlling various cellular functions, such as cell proliferation ( Koeppel et al, 2009 ; Secca et al, 2016 ; Manjur et al, 2019 ; Yao et al, 2019 ; Feng et al, 2020 ), apoptosis ( Koeppel et al, 2009 ; Tinnikov et al, 2009 ; Yeung et al, 2011 ; Feng et al, 2020 ; Li et al, 2020 ), angiogenesis ( Teng et al, 2010 ), cell migration ( Manjur et al, 2019 ; Feng et al, 2020 ), cell differentiation ( Stadhouders et al, 2015 ; Kim et al, 2019 ; Wang et al, 2020a ), inflammation ( Chen et al, 2015 ; Cruz et al, 2017 ; Hari et al, 2017 ; Feng et al, 2020 ; Li et al, 2020 ), and immune response ( Blotta et al, 2009 ; Carneiro et al, 2011 ; Soliman et al, 2014 ; Dorand et al, 2016 ; Secca et al, 2016 ; Wu et al, 2019 ), contributing to physiological homeostasis and the hallmarks of oncogenesis ( Figure 1 ). Different studies have shown the association of IRF2BP2 expression in hematopoietic malignancies and solid tumors, such as breast cancer, leukemia and chondrosarcoma, through mechanisms of gene fusion and point mutations in gene coding sequences, but its exact role and the regulatory mechanism in cancers have not been explored.…”
Section: Biological Functions Of Irf2bp2mentioning
confidence: 99%
“…IRF2BP2 stabilized VGLL4 protein and repressed tumor progression via the inactivation of YAP-TEAD4 complex in liver cancer (41). In contrast, IRF2BP2 repressed the suppressive role of VGLL4 on YAP-TEAD activation and promoted cell growth by inducing CTGF expression in gastric cancer (38). It has also been reported that IRF2BP2 and VGLL4 promote tumor growth through the induction of the immune checkpoint protein programmed cell death-ligand 1 (PD-L1) and immune evasion of tumor cells (43).…”
Section: Vgll4 Is a Tumor Suppressor In Various Types Of Tumormentioning
confidence: 99%
“…Connective tissue growth factor (CTGF), which is also referred to as CCN2, is a small secreted matrix protein that regulates various cellular functions, including proliferation, adhesion, migration, and invasion. [35][36][37][38] Under physiological conditions, CCN2 induces skeletogenesis, angiogenesis, and injury repair. 39 However, pathologically, CCN2 is closely related to cancer bone metastasis.…”
Section: Connective Tissue Growth Factor Utilizes αVβ3 As a Receptor mentioning
confidence: 99%